Digital anatomical measurements and crucial bending areas of the fixation route along the inferior border of the arcuate line for pelvic and acetabular fractures. Issue 1 (December 2016) - Bi, Chun; Ji, Xiaoxi; Wang, Fang; Wang, Dongmei; Wang, Qiugen
Abstract Background Better understanding of three-dimensional (3D) morphology of the pelvis at the area of inferior border of the arcuate line is very important, which could guide the surgeons to treat pelvic and acetabular fractures more efficiently. The objective of this study is to provide references for screw placement and design of anatomical internal fixators for the fixation route along the pelvic inferior border of the arcuate line. Methods Seventy five cases of computed tomography (CT) scan data were collected using Medical Image Database in Shanghai General Hospital between December 2009 and November 2010. 44 males and 31 females, aging from 21 to 91 years (average: 57.8 years) were enrolled. Using MIMICS 13.0, these data were used for three dimensional (3D) reconstructions of pelvic model. A curve from the pubic tubercle, along the inferior border of the arcuate line, to the sacroiliac joint was depicted and then divided into 11 equal parts. The measurements of whole length of the curve, the radius of the curvature and the thickness of bone at each decile point were performed, respectively. Results The thinnest bone thickness at acetabular area was 17.24 ± 2.90 mm and 9.94 ± 2.69 mm for male and female, respectively. The radius of curvature at the decile points 1, 8 and 10 were smaller compared with the surrounding points. Conclusions Using a screw shorter than 10 mm perpendicular to the bone surface along the inferior border of the arcuate line can avoid intra-articular screw penetration. There should be more recontouring of the plate at the areas of pubic tubercle and posterior edge of the acetabulum when placing a fixator along this fixation route. This study provides solid guidance for pelvic and acetabular surgeries as well as designing of anatomical fixators along inferior border fixation route at this area.